ANALISIS IMPLEMENTASI PENDEKATAN PEMBELAJARAN SAINTIFIK PADA MATA PELAJARAN PAI DALAM MENINGKATKAN BERFIKIR KRITIS SISWA DI PKPPS MINHAJURROSYIDIN JAKARTA - Faisal; Syahrullah; Atmowidjoyo, Sutardjo; Asy’ari Akbar, Muh (Almarhalah: Jurnal Pendidikan Islam, 2024)
This research examines the analysis of the implementation of the scientific learning approach in the Islamic Religious Education (PAI) subject at PKPPS Minhajurroosyidiin Jakarta with the aim of enhancing students' critical thinking. The study utilizes a qualitative method, focusing on a series of stages in scientific learning, including planning, design, observation activities, questioning, experiments, data analysis, presentation of results, and learning evaluation. The research findings indicate that this approach successfully increases student engagement, enriches the learning process, and develops critical and creative thinking skills in understanding the teachings of PAI. The effectiveness of the scientific learning approach is evident in several key aspects, such as placing students as active subjects in the learning process, fostering the development of critical thinking skills, increasing student engagement, achieving in-depth learning outcomes, and receiving positive responses from both students and teachers. Factors influencing the implementation of this approach include teacher readiness, the availability of learning resources, school leadership support, student participation, curriculum and evaluation alignment, school culture, as well as understanding and implementation of Islamic values. The synergy among these factors is crucial for the successful implementation of the scientific approach and the enhancement of students' critical thinking in the context of the PAI subject. This research contributes to understanding the practical application of the scientific learning approach in the PAI subject and its impact on improving students' critical thinking. The holistic implementation of this approach requires teacher readiness, school support, student involvement, and a deep understanding of Islamic values. The research results are expected to serve as a foundation for developing more effective learning strategies oriented towards the development of critical thinking skills in students within the context of Islamic education.